Trend of Inequality in the Distribution of Health Care Resources in Iran: - Darzi Ramandi, Sajad; Niakan, Leili; Aboutorabi, Mina; Javan Noghabi, Javad; Khammarnia, Mohammad; Sadeghi, Ahmad (Galen Medical Journal, 2016)
Background: Equity of access to health care services is one of the main goals of health system. Equity in resource distribution in health section constitutes one of the main dimensions of the equity. The aim of the study is determining how doctors, paramedics and hospital beds are distributed in Iran.Materials and Methods: This analytical study was conducted in Iran. Data on 2006-2013 were collected from Statistics Center of Iran and Iran Ministry of Health and Medical Education. After determining the population of 31 provinces and number of physician, paramedics and hospital beds in them, the equal distribution of these facilities and personnel were analyzed using Lorenz curve and Gini coefficient. Stata 12 and DASP2.2 were used for analyzing Gini index. Results: The total number of physicians, paramedics and hospital beds were 37,000, 217,000 and 138,000, respectively in 2013. Tehran as the capital of Iran had the highest percentage of beds among all provinces. The number of physicians, paramedics and hospital beds per 10,000 population of the country were 5.6, 31.3 and 18.5, respectively for 2013. The calculated Gini coefficients for each of them were 0.47, 0.39 and 0.58, respectively.Conclusion: According to Gini coefficients, physicians, paramedics and hospital beds have an unequal distribution throughout the country. However, these distributions are different in different provinces. We recommend creating a comprehensive and continuous monitoring system for equitable allocation of health care resources.[GMJ.2016;5(3):122-130]